Perancangan SOP dan Tata Letak Lantai Produksi Pada LCC Respira V.01 PAPR (Powered Air Purifying Respirator) - Melati Nur Affiyanti; Aprilia Tri Purwandari; Ahmad Juang Pratama (Universitas Al Azhar Indonesia, 2021)
The production process of a tool is very important in a manufacturing company, especially in producing medical equipment. The use of medical masks by health workers in handling COVID-19 patients for hours will make medical personnel uncomfortable when wearing them, one of which is congestion. Therefore, the LCC RESPIRA V.01 PAPR (Powered Air Purifying Respirator) was produced, designed by Mr. Ahmad Juang Pratama, who is a lecturer at Al Azhar University Indonesia. In the production of LCC RESPIRA V.01, a standardization of the production process is needed, so that the reliability of the product can be guaranteed. For this reason, the design of the SOP (Standard Operational Procedure) and the layout of the production floor are carried out in the production process of the LCC RESPIRA V.01 tool. The results of this study include the design of a production SOP in which several departments take part in it, namely team leader, head of the production, production operator, research and development department, head of the warehouse, and quality control department. Besides, a production floor layout design is obtained, where the total production floor area is 8.2 x 6.0 m2 with manual and trolley material handling types.Keywords – Covid-19, Layout production floor, Medical equipment, Standard operational procedure